2009
DOI: 10.1161/circgenetics.108.818062
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Whole-Genome and Candidate Gene Analysis for Response to Statin Therapy in the Treating to New Targets (TNT) Cohort

Abstract: Background-Statins are effective at lowering low-density lipoprotein cholesterol and reducing risk of cardiovascular disease, but variability in response is not well understood. To address this, 5745 individuals from the Treating to New Targets (TNT) trial were genotyped in a combination of a whole-genome and candidate gene approach to identify associations with response to atorvastatin treatment. Methods and Results-A total of 291 988 single-nucleotide polymorphisms (SNPs) from 1984 individuals were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 27 publications
4
132
3
1
Order By: Relevance
“…In the literature, it was shown that the MTHFR C677T polymorphism causes high levels of homocysteine, which can be decreased by statins (1,6). Recent studies suggested that multiple genetic factors, especially MTHFR, which plays a role in the methylation pathway, act for personal therapy (19,20). However, in the present study, we could not find any relationship between the studied polymorphism and impact of statin.…”
Section: Discussioncontrasting
confidence: 84%
“…In the literature, it was shown that the MTHFR C677T polymorphism causes high levels of homocysteine, which can be decreased by statins (1,6). Recent studies suggested that multiple genetic factors, especially MTHFR, which plays a role in the methylation pathway, act for personal therapy (19,20). However, in the present study, we could not find any relationship between the studied polymorphism and impact of statin.…”
Section: Discussioncontrasting
confidence: 84%
“…Several studies analysing the influence of genetic variants on the individual variability of statin efficacy have focused on candidate genes obviously involved in cholesterol metabolism and disease progression. These studies have focused on genes such as the cholesterol receptors LDLR and SCARB1, the cholesterol-metabolizing enzymes HMGCR and CYP7A1, or the cholesterol transporter ABCG8 and ABCA1 [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of HDL-C in disease makes it amenable to candidate-gene and whole-genome association studies (5)(6)(7)(8)(9). Because of the accuracy with which HDL-C can be determined and its high heritability, studies with HDL-C often yield positive results with cholesteryl ester transfer protein (CETP) generally found to be the most highly associated gene.…”
mentioning
confidence: 99%